Methylprednisolone for the Treatment of Patients with Acute Spinal Cord Injuries: A Systematic Review and Meta-analysis. Issue 1 (April 2016) - Evaniew, Nathan; Belley-Côté, Emilie P.; Fallah, Nader; Noonan, Vanessa K.; Rivers, Carly S.; Dvorak, Marcel F.
Introduction: Previous meta-analyses of methylprednisolone for patients with acute traumatic spinal cord injuries (TSCIs) have not addressed confidence in pooled effect estimates and new primary studies have been recently published. We performed a systematic review and meta-analysis to determine whether methylprednisolone improves motor recovery and is associated with increased risks for adverse events. Material and Methods: We searched MEDLINE, EMBASE, and The Cochrane Library for eligible randomized controlled trials (RCTs) and controlled observational studies. Two reviewers independently screened articles, extracted data, and evaluated risk of bias. We pooled outcomes from RCTs and controlled observational studies separately using random effects models. We quantified heterogeneity using the chi-squared test and the I-squared statistic, and we pre-specified subgroup hypotheses to explain potential high heterogeneity. We used the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach to evaluate confidence. Results: We included four RCTs and 17 observational studies. Methylprednisolone did not increase long-term motor score recovery (two RCTs: 335 participants, mean difference [MD] -1.11, 95% CI -4.75 to 2.53, p  = 0.55, low certainty; two observational studies: 528 participants, MD 1.37, 95% CI -3.08 to 5.83, p  = 0.55, very low certainty) or improvement by at least one motor grade (three observational studies: 383 participants, risk ratio [RR] 0.84, 95% CI 0.53 to 1.33, p  = 0.46, very low certainty). Evidence from two RCTs demonstrated superior short-term motor score improvement if methylprednisolone was administered within eight hours of injury (two RCTs: 250 participants; MD 4.46, 95% CI 0.97 to 7.94, p  = 0.01; low certainty), but risk of bias and imprecision limit confidence in these findings. Observational studies demonstrated a significantly increased risk for gastrointestinal bleeding (eight studies: 2727 participants, RR 2.53; 95% CI 1.48 to 4.32; p  < 0.01, very low certainty), but RCTs did not. Risks for other adverse events were not significantly increased. Conclusion: Methylprednisolone does not provide significant long-term benefit to patients with acute TSCIs and may be associated with increased gastrointestinal bleeding. These findings support current guidelines against routine use, but strong recommendations are not warranted because confidence in the effect estimates is limited. This meta-analysis advances current understanding because it includes recent studies not pooled previously and it is the first to consider confidence in the pooled effect estimates. Further research could increase confidence and clarify the influence of potential confounders or effect modifiers.